Odpowiedzi

2009-10-04T19:29:49+02:00
A) (17/3do potegi 0 ) = 1
b) (3/2 do potegi -2) = 4/9
c) ( 1i2/3 do potegi -1) = 3,5
d) (-1.5) do potegi - 3 = -8/27
e) 0,3 do potegi 2 = 9/100
f) 0,01 do potegi - 3 = 1000000
g) (-0,1)do potegi 5 = -0,00001
h) (1,1)do potegi -2 = 100/121
2009-10-04T19:34:55+02:00
A]=1
b]=9\4
c]=-5\3
d]=-125 e] =0,09 f]=-0,000001 g]=1,21
  • Użytkownik Zadane
2009-10-04T19:36:31+02:00
A) Każda liczba podniesiona do potęgi 0 daje zawsze 1 zatem i tu mamy, że (17/3)⁰=1
b) (3/2)⁻²=(2/3)²=(2²/3²)=4/9
c) (1 i 2/3)⁻¹=(5/3)⁻¹=(3/5)¹=(3/5)
d) (-1,5)⁻³=(-1 i 1/2)⁻³=(-3/2)⁻³=(-2/3)³=((-2)³/3³)=(-8/27)
e) 0,3²=(3/10)²=(3²/10²)=(9/100)
f) 0,01⁻³=(1/100)⁻³=(100/1)³=100³=100*100*100=1 000 000
g) (-0,1)⁵=(-1/10)⁵=((-1)⁵/10⁵)=(-1/100000)
h) (1,1)⁻²=(1 i 1/10)⁻²=(11/10)⁻²=(10/11)²=(10²/11²)=(100/121)